1989
DOI: 10.1136/pgmj.65.768.781
|View full text |Cite
|
Sign up to set email alerts
|

Familial malignant retroperitoneal paraganglioma

Abstract: Summary Paragangliomas are neuroendocrine tumours and those occurring in the head and neck have well recognized familial association. Retroperitoneal paragangliomas are uncommon and we present two cases of familial malignant retroperitoneal paraganglioma. Review of the literature revealed marked differences in the incidence and malignant potential of familial and non-familial paraganglioma. In contrast to the cases reported here, familial tumours are generally benign, though they may occur at mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Each of these patients had a solitary extraadrenal paraganglioma, four of which occurred in association with adrenal pheochromocytoma. There have been isolated reports of familial paraganglioma in the literature [25][26][27][28][29][30]. Glowniak et al [26] in 1985 reported familial paraganglioma occurring at the same anatomic location in different family members and suggested that specific genetic abnormalities determine sites of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these patients had a solitary extraadrenal paraganglioma, four of which occurred in association with adrenal pheochromocytoma. There have been isolated reports of familial paraganglioma in the literature [25][26][27][28][29][30]. Glowniak et al [26] in 1985 reported familial paraganglioma occurring at the same anatomic location in different family members and suggested that specific genetic abnormalities determine sites of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 10% of tumors occur outside the adrenal gland. Of extra‐adrenal tumors, chemodectomas and glomus jugulare tumors account for 90%, but they have been reported at many other sites within the head and neck, as well as the mediastinum, retroperitoneum, cauda equina, urinary and the gastro intestinal tract 3,32 …”
Section: Discussionmentioning
confidence: 99%
“…Of extra-adrenal tumors, chemodectomas and glomus jugulare tumors account for 90%, but they have been reported at many other sites within the head and neck, as well as the mediastinum, retroperitoneum, cauda equina, urinary and the gastro intestinal tract. 3,32 Histologically, paragangliomas are composed of spindle (sustentacular) cells and round or polygonal epithelioid cells arranged in a 'Zellballen' pattern. The spindle cells correspond to Schwann cells and are S-100 positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Intraoperatively the tumours appeared solid, homogeneous, and pale brown Paragangliomas are neuroendocrine tumors, and those occurring in the head and neck have well-recognized familial association. Retroperitoneal paragangliomas are uncommon, and their malignant potential has been very rarely reported in literature [4].…”
Section: Discussionmentioning
confidence: 99%